2009
DOI: 10.1073/pnas.0806518106
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic activity-responsive element in the Arc / Arg3.1 promoter essential for synapse-to-nucleus signaling in activated neurons

Abstract: The neuronal immediate early gene Arc/Arg-3.1 is widely used as one of the most reliable molecular markers for intense synaptic activity in vivo. However, the cis-acting elements responsible for such stringent activity dependence have not been firmly identified. Here we combined luciferase reporter assays in cultured cortical neurons and comparative genome mapping to identify the critical synaptic activityresponsive elements (SARE) of the Arc/Arg-3.1 gene. A major SARE was found as a unique Ϸ100-bp element loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
252
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 229 publications
(268 citation statements)
references
References 34 publications
14
252
1
1
Order By: Relevance
“…Previous studies have established that the expression of Arc is activated by neuronal activity (1,2,4,5). Consistent with this finding, we found that the expression of Arc mRNA was also increased by the direct activation of NMDA receptor (NMDAR) with exogenously added NMDA (Fig.…”
Section: Proximal Region Of the Arc Promoter Wassupporting
confidence: 79%
See 3 more Smart Citations
“…Previous studies have established that the expression of Arc is activated by neuronal activity (1,2,4,5). Consistent with this finding, we found that the expression of Arc mRNA was also increased by the direct activation of NMDA receptor (NMDAR) with exogenously added NMDA (Fig.…”
Section: Proximal Region Of the Arc Promoter Wassupporting
confidence: 79%
“…9), although the distal enhancer, SARE, has previously been shown to play a crucial role in activity-dependent Arc expression (4). Arc/Ϫ7000 and Arc/SARE were activated by NMDAR activation, whereas Arc/Ϫ1679 was activated by BDNF or FGF2, but not by NMDA.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…By carefully examining the promoter and the distal regulatory elements critical for activity-dependent neuronal expression, we were indeed able to identify a CRE half-site that functioned as a genuine CREBregulated locus, within the synaptic activity-responsive element (SARE), a distal enhancer region located at about 7-kb upstream of the Arc's transcription start site [54,55]. Strikingly, the SARE of the Arc gene consisted of a unique cluster of binding sites for CREB, MEF2 and SRF/TCF, each of which cooperatively contributed to converting synaptic inputs into a transcriptional output (figure 2b).…”
Section: Input-specificity Of Late Phase Plasticity: a Fascinating Lomentioning
confidence: 99%